Pengukuran Kinerja Keuangan Pasca Merger Dan Akuisisi - Edi Edi; Sylvia Rusadi (Global Financial Accounting Journal, 2017)
This paper examine aneffect of the financial performance of post-merger and acquisition. The financial performance is measured by using ratios, such as return on net worth, return on assets, current ratio, quick ratio, and debt to equity ratio.The samples are firms which did merger and acquisition activity during the years 2003-2011 and that listed on Indonesia Stock Exchange. Data which used in this research is the annual financial report three years before and three years after the mergers and acquisitions by using purposive sampling method. Analysis of the data used to test the hypothesis using paired sample t-test. The results of this study indicate merger firms are having decline performance, debt to equity ratio show significant decline, and other ratios also got decline, though not significant. On the other side, return on net worth and return on assets has significant decline after acquisition, except for current ratio which have insignificant decline after acquisition. Quick ratio and debt to equity ratio has insignificant improvements after acquisition.